Experimental study of thermal rectification in suspended monolayer graphene - Haidong Wang (Nature Portfolio, 2017)
Thermal rectification is instrumental to achieving active heat flow control and energy harvesting in nanoscale devices. Here, the authors demonstrate thermal rectification in asymmetric graphene nanostructures, achieving a large rectification factor up to 26%.